Transcriptome Analysis Reveals PpMYB1 and PpbHLH1 Promote Anthocyanin Accumulation in Phalaenopsis pulcherrima Flowers - Jianqiang Wen; Ji Li; Kunlin Wu; Jingjue Zeng; Lin Li; Lin Fang; Songjun Zeng (Biomolecules, 2025)
Phalaenopsis pulcherrima are known for their captivating floral morphology and diverse colors, demonstrate exceptional resilience to adverse environmental conditions, and exhibit significant potential for hybrid breeding. However, current research on flower coloration is still limited. The data from this study indicates that variations in anthocyanin levels are the primary determinants of the difference between white and purple colors. Through RNA-seq, we identified 469 genes that were differentially expressed. Furthermore, our bioinformatics exploration uncovered two potential transcription factors, PpMYB1 and PpbHLH1, which play regulatory roles in anthocyanin accumulation. Y2H assays demonstrated that these two TFs could form heterodimers and interact with each other. Afterwards, transient expression assays were conducted for the first time in P. pulcherrima flowers, revealing that overexpression of PpMYB1 alone or in combination with PpbHLH1 resulted in purple petal pigmentation. Overexpressing PpMYB1 in tobacco resulted in more purple-colored corollas, stamens, pistils, and pods compared to control plants. Y1H and dual-luciferase assays provided further evidence that PpMYB1 and PpbHLH1 interact with the promoters of the structural genes PpF3H, PpDFR, and PpANS in the anthocyanin biosynthesis pathway, thereby driving their robust expression. This study not only enhances our understanding of the molecular mechanisms underlying anthocyanin synthesis but also holds significant practical implications for advancing plant hybrid breeding and genetic engineering applications in flower color regulation.